Population Aging and Aggregate Consumption in Developing Asia - Gemma Estrada; Donghyun Park; Arief Ramayandi (Asian Development Bank (ADB), 2011)
One of developing Asia's foremost structural economic challenges is the need to rebalance demand and growth toward domestic sources in the face of one of its most significant structural shifts - the demographic transition to an older population. The scope for investment-led growth may be quite limited, so the key to growth is stronger domestic demand, and the key to stronger domestic demand is greater consumption. We examined the impact of the old-age dependency ratio on the share of consumption in the gross domestic products of 31 developing Asian economies and 122 from outside the region from 1998 to 2007. In addition, we tested for a possible difference in its effect in the Asian economies relative to the rest of the sample. The analysis suggests a positive relationship between population aging and consumption though evidence for developing Asia was weaker than that for the rest of the sample. This implies that the aging population may not be contributing as significantly to robust consumption and domestic demand as it does in the rest of the world. In order to rebalance their economies, developing Asian governments must therefore continue to pursue a wide range of policies to promote stronger domestic demand.
hdl:11540/2002
Keywords: 330; Altersvorsorge; Privater Konsum; Nationaleinkommen; Asien